2015
DOI: 10.1002/2015gb005180
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations, origin, and fate of settling diatoms in the Southern Ocean tracked by silicon isotope records in deep sediment traps

Abstract: The Southern Ocean plays a pivotal role in the control of atmospheric CO 2 levels, via both physical and biological sequestration processes. The biological carbon transfer to the ocean interior is tightly coupled to the availability of other elements, especially iron as a trace-limiting nutrient and dissolved silicon as the mineral substrate that allows diatoms to dominate primary production. Importantly, variations in the silicon cycling are large but not well understood. Here we use δ 30 Si measurements to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
39
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 85 publications
13
39
0
Order By: Relevance
“…2). These sinking speeds agree well with those previously estimated by Closset et al (2015) for site 54°S and fall within the range of settling speeds of marine snow and faecal aggregates in the literature (Turner, 2002). consistent with the composition of the sinking diatom assemblages that were overwhelmingly dominated by the heavily silicified Fragilariopsis kerguelensis (up to 96% of the diatom assemblage; Fig.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 2 more Smart Citations
“…2). These sinking speeds agree well with those previously estimated by Closset et al (2015) for site 54°S and fall within the range of settling speeds of marine snow and faecal aggregates in the literature (Turner, 2002). consistent with the composition of the sinking diatom assemblages that were overwhelmingly dominated by the heavily silicified Fragilariopsis kerguelensis (up to 96% of the diatom assemblage; Fig.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…This latter concept would also help to explain the high POC registered during summer 1999-2000, since export food webs tend to lose more organic matter via downward flux (high export efficiency) than retention food webs (low export efficiency) (Dugdale and Goering, 1967;Eppley and Peterson, 1979). In considering these features of our results we hypothesize that the higher valve fragmentation observed in the samples during summer 1999-2000 could be due to other factors different from an intense "grazing event" as suggested previously (Closset et al, 2015). Alternatively, we venture that our sample processing technique may have selectively fragmented the valves of the weakly silicified species of the "high export…”
Section: Accepted Manuscriptsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to marine work (Varela et al, 2004;Closset et al, 2015), lake sediment traps have shown the δ 30 Si signature of diatoms (δ 30 Si diatom ) to be resilient to dissolution and preserved through the water column into the sediment record (Panizzo et al, 2016). Accordingly, δ 30 Si diatom from lacustrine sediment cores can be used to reconstruct past changes in biogeochemical cycling at the catchment/drainage basin scale.…”
Section: Diatomsmentioning
confidence: 86%
“…The influence of environment on δ 30 Si composition in diatoms has yet to be shown under laboratory controlled conditions. Data from in-situ/natural settings, have not documented a species effect (e.g., Cardinal et al, 2007;Fripiat et al, 2012;Closset et al, 2015) although if anything this clearly demonstrates the need to better understand the variability of δ 30 Si in diatoms.…”
Section: Constant Silicon Isotope Fractionation Factormentioning
confidence: 99%